Performance Analysis of Vapour Compression Refrigeration System by Using R134a and Blend of R290 and R600a - Kalambate, Saurabh P.; Gawade, Rajaram N.; Khandekar, Shailesh B.; Jadhav, Dasharath D.; Bhatkar, Naveed M. H. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
In present scenario, most of the industrial and domestic refrigerators working on vapour compression refrigeration cycle are equipped with R134a as a refrigerant. R134a is having zero ozone depletion potential, but it has high global warming potential of 1300.Hence there is need identified for alternative refrigerant to R134a. This research work is focused on performance analysis of vapour compression refrigeration system with regard to COP, refrigerating effect, compressor work for two refrigerants i.e., R134a and blend of R290 and R600a in the proportion of 60%+40% respectively as an alternative refrigerant. Performance measure like compressor discharge temperature is also considered for analysis. The results of blend of R290 and R600a are compared with halogenated hydrocarbon R134a. Trials are conducted for R134a and blend of R290 and R600a. Results showed that COP for R134a refrigerant increases with decreases in evaporator temperature and for blend of R290 and R600a it tries to remain constant. The maximum value of COP achieved for R134a and blend R290and R600a are 3.11 and 4.09 respectively.